2016
DOI: 10.1248/cpb.c15-00780
|View full text |Cite
|
Sign up to set email alerts
|

DNA Topoisomerase Inhibitory Activity of Constituents from the Flowers of <i>Inula japonica</i>

Abstract: Key words Inula japonica; topoisomerase I; topoisomerase IIInula japonica THUNB. (Asteraceae) is a traditional herbal medicine and is widely distributed in Korea, Japan and China, and the flowers of this plant have been used to relieve phlegm, peptic disorder, inflammation and detumescence.1) Some terpenes 2-7) and flavonoids 8,9) have previously been isolated from this medicinal plant and have been reported to possess diverse biological activities, such as anti-diabetes, 10) antihypolipidemia, 11) hepatoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…3, hippeastrine and camptothecin exhibited inhibitory activity on Top I in a similar dose-dependent manner with the IC 50 values at 7.25 ± 0.20 μg/mL and 6.72 ± 0.23 μg/mL, respectively, which clearly implied that hippeastrine was found to be comparable with the well known anticancer drug camptothecin in terms of IC 50 . Other tests on camptothecin against Top I also showed similar inhibitory activity levels with the IC 50 values at 8.71 μg/mL35 or 8.53 μg/mL36, which could further approve our finding in this work. Hence, our result confirmed that hippeastrine could be a potential Top I inhibitor as a very promising anticancer drug candidate, which is in good consistent with the enrichment factors based on UF-LC/MS assay and provides a good validation for its effectiveness.…”
Section: Resultssupporting
confidence: 86%
“…3, hippeastrine and camptothecin exhibited inhibitory activity on Top I in a similar dose-dependent manner with the IC 50 values at 7.25 ± 0.20 μg/mL and 6.72 ± 0.23 μg/mL, respectively, which clearly implied that hippeastrine was found to be comparable with the well known anticancer drug camptothecin in terms of IC 50 . Other tests on camptothecin against Top I also showed similar inhibitory activity levels with the IC 50 values at 8.71 μg/mL35 or 8.53 μg/mL36, which could further approve our finding in this work. Hence, our result confirmed that hippeastrine could be a potential Top I inhibitor as a very promising anticancer drug candidate, which is in good consistent with the enrichment factors based on UF-LC/MS assay and provides a good validation for its effectiveness.…”
Section: Resultssupporting
confidence: 86%
“…[ 28 ] showed an IC 50 of 0.56 μM for camptothecin in a human liver cancer line and Piao et al . [ 31 ] found an IC 50 of 0.70 μM for the same lineage. In addition, Fronza et al .…”
Section: Resultsmentioning
confidence: 99%
“…Tomentosin is a phytochemical sesquiterpene lactone mainly found in medicinal herbs, such as Arnica longifolia , Inula japonica , Inula viscosa , and Xanthium strumarium . 26 29 Tomentosin is known to exert anticancer activity in several types of cancer cells. 16 According to a recent report, tomentosin induces apoptosis and increases the SubG0 and G2/M population in human melanoma cell lines.…”
Section: Discussionmentioning
confidence: 99%